The Development and Deployment of an Online Exam System A Web Application - Islam, Md. Monarul; Nabil, Saifuddin Khaled; Murad, Saydul Akbar; Md Muzahid, Abu Jafar; Raha, Avi Deb; Halder, Monishanker; Gain, Mrityunjoy; Hossain, Md. Bipul; Uddin, K. M. Aslam; Adhikary, Apurba (Asian Journal of Research in Computer Science, 2023)
The rapid advancements in computer technology and the internet’s acceptance in every aspect of our lives, particularly in recent years, have made students and instructors vital in the teaching and learning sector. Web-based studies have also brought about advances in the education area, and numerous applications have become widespread in this field. In this paper, we suggested an online test multiple-choice question assessment system for students called the Online Exam System (OES). This system may be used by any university, college, or institution that has a computerized education system. The OES can be used by teachers to administer quizzes. The system will calculate the participant’s performance based on his response, and the following question will be created based on the participant’s performance. After the examination, the system will display the results and offer feedback based on the participant’s request. Administrative control over the entire system is available. A teacher has authority over the question bank and is responsible for creating test schedules. Therefore, the project will be very helpful for the beginner and mid-level programming learners. And also, will give a proper guideline to the students who are willing to learn programming and introduce the users with competitive programming and problem-solving skills.